Probiotics in irritable bowel syndrome and inflammatory bowel disease: review of mechanisms and effectiveness. Issue 2 (9th March 2023) - So, Daniel; Quigley, Eamonn M.M.; Whelan, Kevin
Abstract : Purpose of review: The gastrointestinal (GI) microbiome has been implicated in the pathogenesis of inflammatory bowel disease (IBD) and has been linked with irritable bowel syndrome (IBS). The aim of this article is to critically review the emerging evidence for the mechanisms and effectiveness of probiotics in the management of these conditions. Recent findings: The GI microbiome is strongly influenced by ageing, diet and disease. Probiotics may confer health effects to the host by modulating the metabolic activities of the microbiome to propagate anti-inflammatory effects and reinforce the intestinal barrier, and are considered to be safe to use. Many short-term studies have demonstrated the effectiveness of probiotics overall in IBS, with meta-analyses demonstrating efficacy across specific strains albeit with relatively small effect sizes. Within IBD, some probiotics appear to offer clinical benefit in ulcerative colitis but strain-specific effects are unclear. Evidence for the use of probiotics in Crohn's disease remains limited. Summary: Probiotics offer considerable potential for the management of IBS and possibly in IBD, however, any benefits conferred appear to be strain-specific. High quality trials of specific probiotics in IBS and IBD, as well as laboratory investigations of their mechanism of action, are required in order to fully understand their potential therapeutic value.